University students’ levels of anxiety, readiness, and acceptance for e-learning during the COVID-19 pandemic - Mee Jay A. Domingo; Karla Auria S. Galeon; Danica Hanna A. Pastor; John Vincent B. Toribio (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This article determined the levels of readiness and acceptance for e-learning of university students during the COVID-19. Participants were 2,035 university students who completed a restricted online survey. Data show that the students are generally ready for e-learning as they exhibit readiness in three of five areas of e-learning readiness (computer self-efficacy, self-directed learning, and learning motivations). However, the students have low mean score ratings for learner control and online communication self-efficacy. As regards their acceptance for e-learning, the data show that the students do not accept all constructs of acceptability such as performance expectancy, attitude, image, social influence, and compatibility. Moreover, results show that the level of online readiness of the students has a strong association with their level of engagement. Hence, the students' motivations for learning, computer/internet self-efficacy, learner control, self-directed learning, and online communication self-efficacy matter for the enhancement of their level of engagement. Further, the researchers learned that anxiety toward COVID-19 does not influence students' levels of e-learning readiness and acceptance; while, their level of readiness is strongly associated with their level of acceptance